Chinese Investment in Latin America : Sectoral Complementarity and the Impact of China's Rebalancing - Ding, Ding (IMF Working Papers; Working Paper ;, 2021)
Over the last decade China's investment in Latin America and the Caribbean (LAC) has increased substantially in volume and become more diversified from natural resources to other industries. Using cross-border mergers and acquisitions data, we demonstrate that since mid-2010s China's overseas investment has tilted toward sectors where China has a comparative advantage in the global markets, a trend similar to that of other major foreign direct investment (FDI) source countries. Moreover, China's rising overseas investment can be linked to the rebalancing of Chinese economy, and LAC stands to benefit from its complementarity vis-a-vis China in sectors where the rising Chinese overseas investment can be met with LAC's own investment gaps. The COVID-19 pandemic could have a long-lasting impact on global value chains and FDI flows, which poses both challenges and opportunities to LAC in attracting FDI, including from China, to support the region's long-run economic development.